The Neolithic chocolate flint mine “Oszybka” in Pakosław, Mazowieckie voivodeship, in the light of the survey of Marcin Bednarz – new approach to old fieldwalk materials - Szubski, Michał; Budziszewski, Janusz; Jakubczak, Michał; Iwański, Mateusz (Acta Archaeologica Lodziensia, 2018)
The flint mine “Oszybka” in Pakosław, Mazowieckie voievodeship was discovered by Marcin Bednarz in 1992 during a field survey on an outcrop of chocolate flint conducted by students practice from Institute of Archaeology University of Warsaw. During the next three seasons about 1750 flint artifacts were collected from the site. This large assemblage contains not only the characteristic forms like cores but also debitage products. Initial research made it possible to determine the chronology of site as belonging to late Mesolithic and/or early Neolithic. Further studies were sadly interrupted by the premature death of Marcin Bednarz. After some years, according to Marcin wishes, team from the Institute of Archaeology Cardinal Stefan Wyszyński University in Warsaw returned to the studies of flint materials from the “Oszybka” flint mine. Thanks to very detailed documentation from the 90s of the last century has become possible to digitalize and integrate it into a GIS environment. As a result, we acquired many spatial analysis of flint materials and combined them with research in terms of technology and typology.